Analysis of Delamination in Two-Dimensional Functionally Graded Multilayered Beam with Non-Linear Behaviour of Material - RIZOV, Victor Iliev (Engineering Transactions, 2018)
An analytical study of delamination fracture in a two-dimensional functionally graded multilayered beam exhibiting material non-linearity is carried-out. The beam is made of adhesively bonded horizontal layers. The material is two-dimensional functionally graded in the cross-section of each layer. A delamination crack is located symmetrically with respect to the beam mid-span. The delamination is studied in terms of the strain energy release rate. The solution derived is compared with the J-integral for verification. The effects of material gradients, the crack location along the beam height and the material non-linearity on the delamination fracture are investigated. The distribution of the J-integral value along the crack front is analysed too.